Copper in colorectal cancer patients: a systematic review and meta-analysis. - Muñoz-Bravo, Carlos; Marín-Burdallo, Inés; González-Herrera, Lucas; González-Palacios Torres, Carla; Lozano-Lorca, Macarena; Jiménez-Moleón, José Juan; Olmedo-Requena, Rocío (Oxford University Press, 2025)
Several clinical studies have evaluated the relationship between copper on colorectal cancer (CRC), but the results are contradictory. This study aimed to conduct a systematic review and meta-analysis to investigate copper measured in two biological matrices (serum/plasma/blood and tissue) and dietary intake in CRC patients compared to healthy controls. We conducted a comprehensive and systematic search in PubMed, Scopus, Embase, and Web of Science. We included studies that reported copper levels in serum/plasma/blood, tissue, or from the diet, with an observational study design (cohort and case–control studies). Study quality was assessed with the Newcastle–Ottawa scale and potential causes of heterogeneity were evaluated. Standardized mean differences (SMD) with 95% confidence interval (CI) were pooled using random-effect models. Overall pooled odds ratio and 95% CI for the risk of CRC were calculated. Twenty-six studies (23 case–control and 3 cohort studies) with a total of 227 354 participants were included. Most of the studies presented low (50%) or moderate quality (42.3%). No differences in serum/plasma/blood copper levels (SMD = 0.23; 95% CI: −0.23, 0.70; I2 = 97.3%, 19 studies), tissue copper levels (SMD = −1.69; 95% CI: −3.41, 0.03; I2 = 85.6%, 2 studies), or copper/zinc ratio (SMD = 1.19; 95% CI: 0.54, 1.84; I2 = 95.3%, 6 studies) were found between CRC patients and healthy controls. Regarding dietary copper, CRC patients had a lower intake (SMD = −0.27; 95% CI: −0.51, −0.03; I2 = 0.0%, 2 studies). No differences were found in copper levels between CRC patients and healthy controls. However, evidence shows mostly low or moderate quality, and results were heterogeneous. More prospective studies with an adequate methodological approach are needed.
Keywords: Colon (Anatomía) - Cáncer; Revisiones sistemáticas (Medicina); Meta-análisis; Carcinógenos; Cobre en el organismo; Copper; Copper/zinc ratio; Colorectal cancer; Cancer; Meta-analysis